PENGARUH LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP DISIPLIN KERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BIMA - Nurhidayah, cici; Firmansyah Kusumayadi (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine the partial significant effect of work environment on employee work discipline, to determine the partial significant effect of organizational commitment on employee work discipline, to determine the simultaneous significant effect of work environment and organizational commitment on employee work discipline at the Department of Population and Registration Bima Regency civil servant. The population in this study were 120 employees consisting of 35 civil servants, 21 honorary employees and 64 non-permanent employees. The sample in this study were 35 civil servants using purposive sampling technique. Data collection techniques include observation, interviews, questionnaires, documentation. Data analysis techniques used validity test, reliability test, multiple linear regression test, classic assumption test, multiple correlation coefficient test, coefficient of determination, t test and f test with the help of SPSS version 22 for windows. The results showed that there was a partial positive and significant effect of the work environment on employee work discipline, there was no partial positive and significant effect of organizational commitment on employee work discipline, there was a positive and significant simultaneous effect of work environment and organizational commitment on employee work discipline in Department of Population and Civil Registration of Bima Regency.